Effectiveness of Participation in Pregnancy Classes to Reduce the Incidence of Obstetric Labor Complications and Cesarean Section - Apriska M. S. Putri; Muhammad P. Mahindra; Mahendra T. A. Sampurna; Rozi A. Aryananda; Fitria K. Khotimah (Indonesian Journal of Obstetrics and Gynecology, 2022)
Objective : to assess the effectiveness of participation in pregnancy classes to inform such a prenatal program for physicians and midwives, focusing to reduce the incidence of obstetric labor complications and cesarean section. Methods : This study was done using an analytic observational approach, using a cross-sectional study and consecutive sampling. One hundred and ninety-four participants of this study were women aged 20–35 years who gave birth between January and November 2019 in balarejo sub-district, East Java, Indonesia. The subjects were divided into two groups: participation (four times) and non-participation (less than four times) in the pregnancy classes. The analyzed outcomes are labor complications (prolonged labor, postpartum hemorrhage, postpartum fever, premature rupture of membrane), and cesarean section birth.. Results: The results of this study indicate that participants of pregnancy classes have a significantly lower probability of suffering prolonged labor (OR=0.05, 95% CI=0.01-0.23, p<0.05), postpartum hemorrhage (OR=0.20, 95% CI=0.04-0.95, p<0.05), and postpartum fever (OR=0.13, 95% CI=0.16-1.08, p<0.05) compared with non-participants. Also, participating women have a lower chance of undergoing cesarean section (OR=0.08, 95% CI=0.03-0.21, p<0.05). Conclusion : The incidence of obstetric labor complications and cesarean section can be effectively reduced by the participation of pregnant woman class.